Concepts of Cloud Computing and Its Applications - Arvind Kumar Shukla; Rajdeep Singh; C K Dixit (AG Volumes, 2022)
In this chapter, the various applications, issues and services of cloud computing have discussed. The concept of Cloud Computing solves the various technical issues to the users for the solution of problems. Virtual abstraction, a technology used in cloud computing, facilitates the quick deployment of applications and data simultaneously reducing the price and complication of the runtime environment, which also enables operations quicker. The overall perception of Cloud Computing is explained here with various services and applications.